DESIGN OF THE INVENTORY APPLICATION OF CV DIVA KARYA MANDIRI USING RAD (RAPID APPLICATION DEVELOPMENT) - Halimah Tus Sadiah; Muhamad Saad Nurul Ishlah (Research Collaboration Community (RCC), 2023)
CV. Diva Karya Mandiri is a CV that is engaged in the production of shoes and sandals for both women and men. In the CV, there are approximately 390 kinds of products, of which 1 product produces more than 10,000 products. There is a large number of production of shoes or sandals so that the number of products that have been produced, the number of products sold and the number of sandals and shoes stored in the warehouse cannot be controlled. At a time when product demand is high, it turns out that the number of products in the warehouse does not match the amount. This study aims to build an inventory application on the Diva Karya Mandiri. The method used in this research is the RAD method which consists of 4 stages: Planning Requirements, User Design, Construction, and Cutover. This study succeeded in building an inventory application that has 11 main menus, namely the dashboard menu which contains a summary of information on goods and user data, goods data menu, supplier menu, incoming goods menu, outgoing goods menu, lending menu, user menu, goods report menu, menu logout, account menu, logout menu. Out of the 11 menus, there are 49 inputs functions tested. The test results show that the average value of the percentage of black box testing using the boundary value analysis method is 95.92%.